Strategi Pengembangan Kawasan Minapadi di Dusun Kemuning, Desa Pledokan, Sumowono - Kusuma Dewi, Patopo (Jurnal Pengabdian kepada Masyarakat Khaira Ummah, 2023)
Minapadi is an integrated cultivation system between agriculture and fisheries. Area-based Minapadi development is very important to support the productivity of the agricultural and fisheries sectors. The research location is in Kemuning, Pledokan Village which has 16.95 Ha of rice fields. For the demplot use an area of ​​2000 m2. The system used is the Minapadi jajar Legawa. The purpose of this study is to examine the advantages of Minapadi system and formulate a strategy for developing the Minapadi area in Kemuning Hamlet. The data processing method uses descriptive qualitative and quantitative analysis. To formulate a strategy using SWOT Analysis. The results showed that in the Minapadi pilot area of ​​Kemuning Hamlet, the rice harvest profit was Rp. 2,607,500, - and from Fish Rp. 5.072.500,- Minapadi business provides 98% profit from conventional rice business. The R/C ratio shows 1.64, so Minapadi agribusiness is feasible to run due to improving society welfare. The development strategy based on the results of the SWOT analysis includes providing advocacy to relevant stakeholders, outreach to farmer groups/pokdakan, making demonstration plots for Minapadi areas as well as monitoring and evaluation. Keywords: Minapadi system, Development strategy, Produktivity, Social Welfare .